Analysis of Building Electrical Energy Consumption and Energy Saving Potential Using e-Quest Simulation with the Energy Efficiency Measures Method - Rano Hanif; Arwizet K; Yolli Fernanda; Andre Kurniawan (Unversitas Negeri Padang, 2026)
This study presents a preliminary electrical energy audit of the Health Office Building of West Sumatra Province, aiming to determine the building's Energy Consumption Intensity (ECI), map the distribution of electrical loads, and identify Energy Efficiency Measures (EEM) through e-Quest building energy simulation. A descriptive-quantitative method was applied following the SNI 6196:2011 energy audit procedure and the ECI standard of Ministerial Regulation of Energy and Mineral Resources (ESDM) No. 13 of 2012. Primary data were obtained from direct field measurement of voltage, current, and power factor using a watt meter across 22 rooms on two floors (1,360 m2), supplemented by 12 months of PLN electricity billing data as secondary data. Building simulation was performed in the e-Quest Quick Energy Simulation Tool using Activity Area, Lighting, and Plug Loads parameters derived from the field measurements. The manual calculation yielded a total consumption of 78,337.13 kWh/year, corresponding to an ECI of 57.60 kWh/m2/year, validated against PLN billing data with a deviation of only 5.00%, placing the building in the